Pengaruh Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT Bank Mandiri Taspen Bekasi - Egga Aulia (CV Edujavare Publishing, 2024)
The organization's goal is to achieve high productivity by conducting employee performance assessments to determine the extent to which employees are able to play a role in the development and growth of the company in order to keep up with times of change and very tight competition. In an organization or company, not all performance produced by employees always produces good results, because the performance level of each employee is different, and each employee also has their own way of improving their performance. This research aims to examine the influence of organizational culture and organizational commitment on employee performance. The population of this research is all employees of PT Bank Mandiri Taspen Bekasi Branch Office. The sampling method in this research uses a saturated sampling method. The sample in this study was 35 employees of PT Bank Mandiri Taspen Bekasi Branch Office. The data analysis methods used in this research are descriptive statistics, data quality testing, and hypothesis testing. The results of this research indicate that organizational culture and organizational commitment have a significant effect on employee performance. The results of this research show that organizational culture has a significance value of 0.02<0.05, which means that H1 is accepted and H0 is rejected, so that organizational culture has a significant effect on employee performance. Apart from that, the organizational commitment variable has a significance value of 0.04<0.05, which means that H2 is accepted and H0 is rejected, so that organizational commitment has a significant effect on employee performance.